Practical Approaches to Genetic Code Expansion with Aminoacyl-tRNA Synthetase/tRNA Pairs - Anton Natter Perdiguero; Alexandria Deliz Liang (CHIMIA, 2024)
Genetic code expansion (GCE) can enable the site-selective incorporation of non-canonical amino acids (ncAAs) into proteins. GCE has advanced tremendously in the last decade and can be used to create biorthogonal handles, monitor and control proteins inside cells, study post-translational modifications, and engineer new protein functions. Since establishing our laboratory, our research has focused on applications of GCE in protein and enzyme engineering using aminoacyl-tRNA synthetase/tRNA (aaRS/tRNA) pairs. This topic has been reviewed extensively, leaving little doubt that GCE is a powerful tool for engineering proteins and enzymes. Therefore, for this young faculty issue, we wanted to provide a more technical look into the methods we use and the challenges we think about in our laboratory. Since starting the laboratory, we have successfully engineered over a dozen novel aaRS/tRNA pairs tailored for various GCE applications. However, we acknowledge that the field can pose challenges even for experts. Thus, herein, we provide a review of methodologies in ncAA incorporation with some practical commentary and a focus on challenges, emerging solutions, and exciting developments.